Catastrophic Aortoenteric Fistula Due to an Eroding Bare Metal Duodenal Stent - Stuart, Ryan (Cureus, 2021)
Deployment of bare metal duodenal stents for individuals with gastric outlet obstructions (GOOs) is a well-characterized measure to improve the quality of life. However, these interventions are palliative in nature and are associated with known complications. We present an unfortunate case of a previously not well described, albeit not surprising, a complication of stent placement. The individual underwent duodenal stent placement due to obstructive metastatic disease and subsequently presented for gastrointestinal (GI) bleed. It was determined that an aortoduodenal fistula acutely developed and, despite heroic efforts, the patient ultimately expired.